2003
DOI: 10.1007/s00438-003-0873-8
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced expression of the DNA damage-inducible gene DIN7 results in increased mutagenesis of mitochondrial DNA in Saccharomyces cerevisiae

Abstract: We reported previously that the product of DIN7, a DNA damage-inducible gene of Saccharomyces cerevisiae, belongs to the XPG family of proteins, which are involved in DNA repair and replication. This family includes the S. cerevisiae protein Rad2p and its human homolog XPGC, Rad27p and its mammalian homolog FEN-1, and Exonuclease I (Exo I). Interestingly, Din7p is the only member of the XPG family which specifically functions in mitochondria. We reported previously that overexpression of DIN7 results in a mito… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
17
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 32 publications
0
17
0
Order By: Relevance
“…It has been shown that overexpression of Din7 destabilizes poly(GT) in mtDNA and enhances gross rearrangements in mtDNA, presumably due to enhanced recombination (129). The Sia group has shown that loss of the Din7 function does not significantly affect repeat-mediated mtDNA deletions, but it synergizes with the G776D allele of MSH1 (see below) to increase this particular recombination-based process (130).…”
Section: Exonucleasesmentioning
confidence: 99%
“…It has been shown that overexpression of Din7 destabilizes poly(GT) in mtDNA and enhances gross rearrangements in mtDNA, presumably due to enhanced recombination (129). The Sia group has shown that loss of the Din7 function does not significantly affect repeat-mediated mtDNA deletions, but it synergizes with the G776D allele of MSH1 (see below) to increase this particular recombination-based process (130).…”
Section: Exonucleasesmentioning
confidence: 99%
“…Among the constitutive mitochondrial nucleases in Saccharomyces cerevisiae are the Nuc1 nuclease that contributes to DNA recombination efficiency and functions in apoptosis (4,38) and the Cce1 endonuclease that resolves recombination intermediates (29). The Din7 endonuclease is a mitochondrially located 5Ј flap endonuclease related to FEN1 (20). While deletion of the gene for either of these enzymes produced marginal mitochondrial phenotypes, more severe phenotypes were observed when combined deletions of these nuclease genes were studied or when they were combined with deletions of other genes involved in DNA recombination or repair, such as MHR1 or MSH1 (20,22,27).…”
mentioning
confidence: 99%
“…The Din7 endonuclease is a mitochondrially located 5Ј flap endonuclease related to FEN1 (20). While deletion of the gene for either of these enzymes produced marginal mitochondrial phenotypes, more severe phenotypes were observed when combined deletions of these nuclease genes were studied or when they were combined with deletions of other genes involved in DNA recombination or repair, such as MHR1 or MSH1 (20,22,27). Recently, human Dna2 was shown to localize to both the nuclear and mitochondrial compartments and to participate in mitochondrial DNA replication and base excision repair (11,39).…”
mentioning
confidence: 99%
“…The DIN7 gene codes for a mitochondrial protein homologous to the S. cerevisiae Exo1p, Rad2p, and the flap endonuclease Rad27p (Mieczkowski et al 1997;Fikus et al 2000). Overexpression of Din7p results in a twofold increase in recombination between mutations at the cytb gene that are 1 kb apart (Koprowski et al 2003). Although these proteins have biochemical activities consistent with a role in recombination, their loss has not been demonstrated to result in a substantial defect in this process in vivo.…”
mentioning
confidence: 99%